The pragmatic aspects and their relationship with the theatrical discourse - Abdulrdha, Ola Ahmed; Nasser, Esam Ahmed (Al-Adab Journal, 2022)
One of the most important contemporary approaches that has a clear impact on the analysis of artistic works is the pragmatic approach, which is a linguistic approach that studies the relationship between linguistic activity and its users, the forms and methods of using linguistic signs and the different contexts in which the speech is made, since language is one of the most powerful tools that the sender uses to communicate his intentions to the recipient and influence him according to these purposes and to look for the factors that make the speech a clear and successful communicative message. Pragmatics has been applied in the Koran, the short story, the novel, poetry and the theater, and in our opinion, there is no text that embodies pragmatics more than the theatrical text, due to the predominance of its dialogical nature, because the function language is the function of communication. In this research we ask ourselves a series of questions, which are the following: - What is pragmatics? - What is the nature of the relationship between the theatrical text and pragmatics? Are the works subject to deliberative analysis? - How is the play analyzed according to the pragmatic approach? Is it possible to talk about pragmatics in theatrical discourse? Or, can pragmatics be used as a means in the study of theatrical discourse? Pragmatics has opened new horizons for the researcher to allow him to investigate, analyze, and accurately understand language and discourse, and therefore the choice of this research, marked with: "The pragmatic aspects and their relation to theatrical discourse", for reasons that include: pragmatics is an important science, and the interest in the theatrical pragmatic dimension is modern, which aroused the desire to know it more in the field of theatrical analysis.